Application of Two Rowed Weyl Module in the Case of Partition (7,6) and Skew- Partition (7,6)/(1,0) - Hatim, Nejood A.; Hassan, Haytham R. (Iraqi Journal of Science, 2021)
The aim of this work is to study the application of Weyl module resolution in the case of two rows, which will be specified in the partition (7, 6) and skew- partition (7,6)/(1,0) by using the homological Weyl (i.e. the contracting homotopy and place polarization).